ANALISIS MANAJEMEN RANTAI PASOK TELUR AYAM RAS PETELUR PT GLOBAL BUWANA FARM DENGAN METODE FSCN - Talitha Nariswari Nurjannah; Sandrina Dewi Lestari; Firdha Yuanda Kusdamayanti; Anjeli Apriliana (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstract. Global Buwana Farm is a layer farming business that was established in 2013. The farm is owned and led by Mr. Gerry Buwana. It is located in Cihideung Ilir, an area in Bogor Regency, West Java. The main focus of the business is the development of the Lohman breed of laying hens, which is known for its high productivity in producing eggs. This study analyzed the supply chain of layer chicken farms at PT Global Buwana Farm in Bogor Regency using the Food Supply Chain Networking (FSCN) method. The results showed that PT Global Buwana Farm emphasized the need for effective supply chain management, appropriate distribution strategies, cooperation between supply chain members, and attention to logistics. It is recommended that the company improve logistics management, pay attention to egg quality, diversify products with omega-3 eggs, and improve cooperation and information technology to increase business efficiency. Keywords: Food Supply Chain Networking, Layer Chicken Farms, Logistics, Supply Chain. Abstrak. Global Buwana Farm adalah sebuah usaha peternakan ayam petelur yang didirikan pada tahun 2013. Peternakan ini dimiliki dan dipimpin oleh Bapak Gerry Buwana. Lokasinya berada di Cihideung Ilir, sebuah daerah di Kabupaten Bogor, Jawa Barat. Fokus utama dari usaha ini adalah pengembangan ayam ras petelur jenis Lohman, yang dikenal karena produktivitasnya yang tinggi dalam menghasilkan telur. Penelitian ini menganalisis rantai pasok peternakan ayam ras petelur di PT Global Buwana Farm di Kabupaten Bogor dengan menggunakan metode Food Supply Chain Networking (FSCN). Hasil penelitian menunjukkan bahwa PT Global Buwana Farm menekankan perlunya manajemen rantai pasok yang efektif, strategi distribusi tepat, kerjasama antar anggota rantai pasok, dan perhatian pada logistik. Disarankan agar perusahaan meningkatkan pengelolaan logistik, memperhatikan kualitas telur, diversifikasi produk dengan telur omega-3, serta meningkatkan kerjasama dan teknologi informasi untuk meningkatkan efisiensi bisnis. Kata kunci: Food Supply Chain Networking, Logistik, Peternakan Ayam Ras Petelur, Rantai Pasok.